2020
DOI: 10.1007/s11432-019-2763-5
|View full text |Cite
|
Sign up to set email alerts
|

Leader-following flocking for unmanned aerial vehicle swarm with distributed topology control

Abstract: To address the flocking issues of an unmanned aerial vehicle (UAV) swarm operating at a leaderfollower mode, distributed control protocols comprising both kinetic controller and topology control algorithm must be implemented. For flocking the UAV swarm, a distributed control-input method is required for both maintaining a relatively steady state between neighboring vehicles (including velocity matching and distance maintenance) and avoiding vehicle-to-vehicle collision. Furthermore, the stability of control pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Liu et al [67] suggested a kinetic controller, distributed β-angle test (BAT)-based topology control algorithm, and Flying ad-hoc network (FANET) for UAV flocking. This mechanism could perform neighbor selection and reduce the communication overhead significantly.…”
Section: Related Surveymentioning
confidence: 99%
“…Liu et al [67] suggested a kinetic controller, distributed β-angle test (BAT)-based topology control algorithm, and Flying ad-hoc network (FANET) for UAV flocking. This mechanism could perform neighbor selection and reduce the communication overhead significantly.…”
Section: Related Surveymentioning
confidence: 99%
“…In our work, we apply the behavior of flocks of starlings following a topological interaction rule in order to achieve robust swarm flight behavior [19]. In prior works, this type of biological insight has inspired flocking control design [20] and real-world deployment of drone swarms [21]. Somewhat more related, [22] implements end-to-end-learned flocking control based on classical swarming models.…”
Section: Related Workmentioning
confidence: 99%
“…Autonomous ight and evasion control of swarm system has become an urgent problem to be solved. For a swarm system, there are currently two main control methods: leader follower [5][6][7] and behavior control [8][9][10]. e idea of the leader follower method is to introduce a leader and use the distributed control method to control other followers in the swarm, so that the state (such as speed) of all followers gradually follows the leader and nally achieves consistency.…”
Section: Introductionmentioning
confidence: 99%